Synthesis and Antibacterial Screening of Some Novel Isoxazole Derivatives: Research Article (Journal of Pharma Insights and Research, 2024)
The emergence of antimicrobial resistance necessitates the development of novel antibacterial agents. This study focuses on the synthesis, characterization, and antibacterial evaluation of a series of N3, N5-di(substituted)isoxazole-3,5-diamine derivatives (178a-f) as potential antibacterial agents. The compounds were synthesized using a two-step process involving the formation of N1, N3-di(substituted)malonamide intermediates followed by cyclization with hydroxylamine hydrochloride under microwave irradiation. All synthesized compounds were thoroughly characterized using spectroscopic techniques including IR, 1H-NMR, and mass spectrometry to confirm their structural integrity. The antibacterial activity of the synthesized compounds was evaluated using the Mueller Hinton broth turbidometric method against both Gram-negative (Escherichia coli MTCC 443) and Gram-positive (Staphylococcus aureus MTCC 96) bacterial strains. The minimum inhibitory concentration (MIC) was determined for each compound and compared with the standard drug cloxacillin. Among the synthesized derivatives, compounds 178d, 178e, and 178f exhibited the most potent antibacterial activity. Against E. coli, these compounds showed MIC values of 117 μg/mL, 110 μg/mL, and 95 μg/mL, respectively, surpassing the activity of cloxacillin (MIC 120 μg/mL). Similarly, against S. aureus, compounds 178d and 178e demonstrated superior activity with MIC values of 100 μg/mL and 95 μg/mL, respectively, compared to cloxacillin (MIC 100 μg/mL). Structure-activity relationship analysis revealed that the presence of electron-withdrawing groups (F, Cl) and para-substitution on the phenyl rings generally enhanced antibacterial activity. In conclusion, this study presents a series of novel N3, N5-di(substituted)isoxazole-3,5-diamine derivatives with promising antibacterial activity against both Gram-negative and Gram-positive bacteria